The Palemon Myth in Samogitia: The Second Half of the Eighteenth Century to the Early Twentieth Century - Gudmantas, Kęstutis (Senoji Lietuvos literatūra, 2025)
According to the myth of the Roman origin of the Lithuanians recorded in sixteenth-century Lithuanian chronicles, it was Samogitia where Palemon arrived first, and ‘Lithuania started to expand from the Samogitians’. The myth was further developed and originally interpreted by Maciej Stryjkowski (Kronika Polska, Litewska, Żmodźka y wszystkiey Rusi, 1582) and Wojciech Wijuk-Kojałowicz (Historia Litvana, 1650). The reprint of Stryjkowski’s Kronika (1766), the appearance of Franciszek Paprocki’s compendium (first edition in 1760, later editions in 1763, 1771, and 1775), and the former Jesuit Mikołaj Wieliczko, who was the parish priest of Seredžius from 1774 to 1779, should possibly be linked to the emergence of the toponym ‘Palemono kalnas’ (Palemon Hill) in Seredžius (first mentioned in 1779, in the inventory of the Seredžius church). During the first half of the nineteenth century, we see a veritable renaissance of the Palemon myth in Samogitia:(1) the proponents of the myth were the ‘literati’ Dionizy Paszkiewicz (Dionizas Poška), Ludwik Jucewicz, Sylwester Walenowicz (Silvestras Valiūnas), Samogitian Bishop Józef Arnulf Giedroyć, and others(2) a significant number of the Samogitian elite of the time were members of the ‘Palemon’ Masonic Lodge(3) Michał Zaleski, a landowner from Veliuona, erects a monument to Palemon;(4) the Samogitian nobility trace their ancestry back to the mythical founder of Lithuania and Samogitia (cf. the Gimbutas family tree based on various texts from the eighteenth to the mid-nineteenth century)(5) in the mid-to-late nineteenth century, Palemon continued to ‘live on’ in calendars and became a character in fabricated ‘folklore’.It must be noted that the nineteenth century was dominated not by the theory of purely Roman origin, but by Herulian, Herulian-Roman, and Scandinavian theories of the origin of the Lithuanians and Samogitians. Some authors propose combinations of these versions. Accordingly, Palemon could have been a Herulian, a Roman, a Scandinavian, or even an autochthon.The facts presented point to an intense reception of the Palemon myth, which should be explained by the increased dissemination of historical knowledge in the society of that time and the relatively strong regional identity of Samogitia.
Keywords: Palemon; myth; Samogitia; reception; topography